2018
DOI: 10.3390/geosciences8020048
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Simplified Connectivity Index and Specific Sediment Potential in River Basins by Means of Geomorphometric Tools

Abstract: Sediment connectivity is a major topic in recent research because of its relevance in the characterization of the morphology of river systems and assessing of sediment transport and deposition. Currently, the connectivity indices found in the literature are generally dimensionless and need to be coupled with quantitative soil-loss data for land management and design purposes. In the present work, a simple methodology is proposed to assess two different indices, namely, the simplified connectivity index (SCI) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 30 publications
0
18
0
1
Order By: Relevance
“…Hydrological connectivity is a term often used to describe the linkages between runoff and sediment generation in the upper parts of catchments and the receiving waters [44]. The use of the connectivity index as an input parameter for SDR has shown satisfying results globally [45][46][47][48]. For this study, the calculation of the connectivity index, and subsequently SDR, was implemented in ArcMap 10.5 as described in [49] based on the following formula:…”
Section: Sediment Delivery Modelmentioning
confidence: 99%
“…Hydrological connectivity is a term often used to describe the linkages between runoff and sediment generation in the upper parts of catchments and the receiving waters [44]. The use of the connectivity index as an input parameter for SDR has shown satisfying results globally [45][46][47][48]. For this study, the calculation of the connectivity index, and subsequently SDR, was implemented in ArcMap 10.5 as described in [49] based on the following formula:…”
Section: Sediment Delivery Modelmentioning
confidence: 99%
“…Sediment connectivity in river basins has attracted a lot of attention in recent years (Fryirs et al ., 2007a; Cavalli et al ., 2013; Fryirs, 2013; Fryirs and Gore, 2013; Foerster et al ., 2014; Bracken et al ., 2015; Grauso et al ., 2018; Heckmann et al ., 2018) and most studies have focused on understanding the potential of sediment transfer from source to sink in small river catchments. In one of the very few studies on large river basins, the upper Kosi basin in Tibet and Nepal, remarkable spatial variability in sediment connectivity has been demonstrated (Mishra et al ., 2019) which has been discussed in the previous section.…”
Section: Future Perspectives On Connectivity Researchmentioning
confidence: 99%
“…Recent studies have reported the necessity of developing accurate modelling tools for geomorphic investigation of sediment pathways, cross-scale connectivity processes and how overland flow inputs change from various sources, but keeping simplified mathematical and computational methodologies (Williams et al, 2016;Cossart and Fressard, 2017;Grauso et al, 2018). The new approach presented in this study to compute FSC kept the simple mathematical structure of the well known Borselli's index of FSC and increased the number of inputs at the same time.…”
Section: Original and Aggregated Index Of Connectivitymentioning
confidence: 99%